Work-in-Progress Inventory Control Case Study in Lean Management - Wai Tan, Hong; Rijal Jamaludin, Khairur; S Hamzah, H (International Journal of Engineering and Technology, 2018)
Increasing the rate of converting raw material into finished product and delivering it on time is a main driver for each manufacturing industry to achieve continuous improvement in its business operation.Â This case study demonstrates the improvement of the work-in-progress inventory in a non-lean company seeking to adopt lean management.Â Introducing the value stream mapping (VSM) lean technique to identify the waste in the current production operation. A selection of lean tools such as Kanban card, supermarket racking and one-piece flow are applied to control and monitor the WIP inventory after justification of the factors (process cycle time, production facilities layout and facilities capacity allocation) that influence the change from the current production operation situation. The construction of the current VSM had identified the major waste in WIP inventory handling in the final fabrication process.Â The fluctuation of WIP inventory has been resolved by the implementation of supermarket racking; therefore, an improvement base for WIP inventory control has been established.Â Throughout this study, the lean management concept had been fostered into the production floor team and will continue developing to the organization. Â